Computational analysis of hybrid nanofluid enhanced heat transfer in cross flow micro heat exchanger with rectangular wavy channels. (April 2021) - Ghachem, Kaouther; Aich, Walid; Kolsi, Lioua
Abstract: The current paper provides a three-dimensional computational analysis of hybrid nanofluid enhanced heat transfer in cross flow micro heat exchanger with rectangular wavy channels. This micro heat exchanger is assumed to be well insulated from its surrounding and made respectively of five top and five bottom channels. The hot and cold nanofluids flow through the upper and lower cross channels, respectively. This analytical investigation has been carried out using the finite element method with a wide range of governing parameters such as the flow velocity (5 mm/s ≤ u ≤ 100 mm/s), the wave number (0 ≤ N ≤ 20) and the nanoparticles concentration (0 ≤ ϕ ≤ 0.05). It was concluded that an adequate choice of flow velocity and nanoparticles volume fraction can minimize the heat exchanger size and the addition of nanoparticles has significant effect only with high velocities (u ≥ 50 mm/s). Moreover, it was revealed that a trade-off between the relevant controlling parameters is required to ensure an optimal efficiency. The highest heat exchanger efficiency was achieved with a wave number N = 8, a nanoparticles concentration ϕ = 0.05 and an inlet velocity u = 50 mm/s.